Water and food in the bioeconomy: Challenges and opportunities for development - Rosegrant, Mark W.; Ringler, Claudia; Zhu, Tingju; Tokgoz, Simla; Bhandary, Prapti (Wiley, 2013)
The world economy is under pressure for greater, more efficient and more sustainable use of natural resources to meet complementary and competing objectives in the food, water and energy sectors. Interactions between these three sectors have become increasingly affected by the bioeconomy—a concept that encompasses economic growth driven by the development of renewable biological resources and biotechnologies to produce sustainable products, employment and income. This article explores how water and the bioeconomy are interlinked, including how the constraints from growing water scarcity—in part caused by development of the bioeconomy—may influence bioeconomic growth. The article describes the impact of biofuel production on water quantity and quality and examines the potential for improved water use through the development of crop biotechnology and improved crop management. Then alternative scenarios for water in the bioeconomy are assessed, and policy conclusions are presented.